Experimental and Numerical Investigation of the Electromechanical Behavior of High Temperature Superconducting Tapes and Cables Subjected to Various Mechanical Loads - Allen, Nathaniel. (2017)
Abstract: Second generation high temperature superconducting (HTS) tapes have great mechanical properties as well as excellent high current and high field capabilities. These characteristics make them a very promising conductor for applications like accelerator and fusion magnets. Several HTS tape cabling methods are under development for these magnet applications. To improve fabrication methods and maximize operational performance of these cables composed of several HTS tapes, it is necessary to characterize both the electromechanical behavior of the full scale cables and of the individual tapes under anticipated thermal, mechanical and electromagnetic loads. In this work, laboratory experimentation and structural finite element analysis have been used to investigate the electromechanical behavior of single HTS tapes and cables. Experiments were conducted to evaluate critical current performance, the maximum current a superconductor can carry before becoming resistive, under various loads while finite element analysis was used to analyze the strain dependence of that critical current for each load type. Single tape experiments were conducted on three types of commercially available HTS tapes under pure torsion, axial tension, combined tension-torsion and transverse compression on their wide face and thin edge. The results from the tests indicate single HTS: under pure torsion had no reduction in critical current down to a twist pitch of 120 mm; under axial tension experienced a sharp irreversible critical current degradation at their yield strength; under combined tension-torsion behaved similar to pure tension samples for twist pitch lengths greater than 150 mm; and under transverse compression were far more sensitive to loads applied on their thin edge compared to their wide face. The single HTS tapes were also analyzed under the same loading conditions using structural finite element analysis. A novel technique was developed for modeling the layered composite structure of the HTS tapes using structural solid-shell elements. The numerical model was able to closely replicate the experimental stress-strain curves and torque behavior of each type of tape. The simulations also produced detailed axial strain results which were successfully paired with an analytical model to predict the critical current performance of the tapes. The numerically predicted critical current was found to have close agreement with the experimental results for each load type. In addition to the single tape work, electromechanical experiments on two HTS cabling methods, designed for high field magnet applications, were conducted. The HTS cable-in-conduit conductor (CICC) was tested under bending down to a diameter of 0.25 m and revealed that the minimum safe bending diameter to avoid critical current degradation was 0.5 m. The twisted stacked-tape cable (TSTC) was tested under mechanical transverse compression and overall performed better than expected based on real electromagnetic load degradations seen during high field tests. Both HTS cabling methods were also analyzed using finite element analysis. A methodology for modeling full scale three-dimensional HTS cables was developed incorporating contact pair relationships for modeling the relative motion between tapes. The full scale cables were simulated under bending and electromagnetic transverse compression. Their numerical strain results were validated against analytical models and were used to predict the critical current performance of the cable as done for single tape. The HTS CICC model under bending agreed well with the experimental critical current results for a nearly frictionless case having a coefficient of only 0.02, indicating the tapes can slide freely during bending. The TSTC model under transverse compression found that a solid cylindrical copper core provides the best support for the tapes under electromagnetic loads. The overall agreement seen between the experimental measurements and the finite element analysis validates the electromechanical characteristics of the tapes and cables presented in this work. Together the numerical and experimental results provided new details about the strain dependence of the critical current for each load type.; Thesis (Ph.D.)--Tufts University, 2016.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Luisa Chiesa.; Committee: Makoto Takayasu, Gary Leisk, Michael Zimmerman, and Thomas Vandervelde.; Keywords: Mechanical engineering, and Canadian history.